Performance of Imaging Techniques in Non-invasive Diagnosis of Non-alcoholic Fatty Liver Disease in Children: A Systematic Review and Meta-Analysis - Yu, Qun; Liu, Yiwei; Hu, Peipei; Gao, Feng; Huang, Guoqing (Frontiers in Pediatrics, 2022)
Background and Aim Non-alcoholic fatty liver disease (NAFLD) has become the most common chronic liver disease in children. With the continuous emergence of various non-invasive diagnostic methods, imaging techniques have always been considered as potential alternative methods to liver biopsy. This study aimed to evaluate the diagnostic performance of imaging techniques so as to search for the most promising technology. Methods We searched English and Chinese databases. English databases included Cochran library, Embase, PubMed, and Web of Science, while Chinese databases included the Wanfang database and China National Knowledge Internet. Results Finally, 11 articles were included (12 studies, one of which included studies on both fibrosis and steatosis). Further, 26.2% of the participants had mild steatosis, 34.1% had moderate steatosis, and 34.9% had severe steatosis. Also, 64.0% had any fibrosis, 29.1% had significant fibrosis, 13.8% had advanced fibrosis, and 2.8% had cirrhosis. Irrespective of the grade of fibrosis, transient elastography (TE) had higher sensitivity (97–100%), whereas magnetic resonance elastography (MRE) had the lowest sensitivity (58–63%). The pooled sensitivity and specificity of imaging techniques in diagnosing steatosis were 89% (95% CI, 71–96) and 89% (95% CI, 72–96), and AUROC 0.95 (95% CI, 93–97), multifrequency magnetic resonance elastography-hepatic fat fraction (mMRE-HFF) had the highest sensitivity (87%, 95% CI 77–97), ultrasonography (US) had the lowest specificity (96%, 95% CI 92–98%). Conclusion Imaging techniques have a good diagnostic performance for children with NAFLD, especially the diagnosis of liver fibrosis based on ultrasound or magnetic resonance elastography. Compared with different imaging techniques, TE has the best performance in diagnosing significant fibrosis. Liver stiffness measurement (LSM) is expected to become a biological indicator for routine screening, dynamic monitoring of disease changes, and prognostic evaluation.